Aeroacoustic noise prediction of a vertical axis wind turbine using large eddy simulation. Issue 8 (November 2021) - Aihara, Aya; Bolin, Karl; Goude, Anders; Bernhoff, Hans
This study investigates the numerical prediction for the aerodynamic noise of the vertical axis wind turbine using large eddy simulation and the acoustic analogy. Low noise designs are required especially in residential areas, and sound level generated by the wind turbine is therefore important to estimate. In this paper, the incompressible flow field around the 12 kW straight-bladed vertical axis wind turbine with the rotor diameter of 6.5 m is solved, and the sound propagation is calculated based on the Ffowcs Williams and Hawkings acoustic analogy. The sound pressure for the turbine operating at high tip speed ratio is predicted, and it is validated by comparing with measurement. The measured spectra of the sound pressure observed at several azimuth angles show the broadband characteristics, and the prediction is able to reproduce the shape of these spectra. While previous works studying small-scaled vertical axis wind turbines found that the thickness noise is the dominant sound source, the loading noise can be considered to be a main contribution to the total sound for this turbine. The simulation also indicates that the received noise level is higher when the blade moves in the downwind than in the upwind side.